Foot injuries in elite handball players - Carlino, G. (Education. Physical training. Sport)
The objective was to value the incidence of foot injuries in professional handball players working in Italy and to identify a number of possible types of preventive measures. Materials & Methods: The group was formed by 118 professional athletes (49 males and 69 females) who played in the Italian national teams. We registered and examined all foot injuries requiring interruption of sport activity for more than one day which occurred during training sessions and competitions of the Italian national handball teams over a period of two years (from March 1997 to March 1999). Twenty-seven players out of 118 (22.8%) incurred in foot injuries, 13 (26.5%) males and 14 (20.3%) females. Some athletes suffered more than one foot injury, but none often sustained any injury in other anatomical sites, during the period of observation. Results: A total of 31(26.3%) foot injuries were recorded, 14 (28.6%) in males and 17 (24.6%) in females. Overuse injuries represented 61.3% of all injuries, followed by traumatic injuries (25.8%), degenerative pathology (9.7%) and neurologic pathology (3.2%). With reference to traumatic injuries ankle sprain was the most frequently seen with six cases (74% of all traumatic injuries), four (66.7%) in inversion and two (33.3%) in eversion. With regard to degenerative pathology we found two cases (6.5%) of ankle joint chondropathy and one case (3.2%) of fibrose impingement of the ankle joint. A case of tarsal tunnel syndrome was relevant to neurologic pathology. As regards preventive measures ninety athletes (76.3%) did not use any device of passive prevention, thirteen (11%) used ankle taping, eight (6.8%) consistently and five (4.2%) discontinuously; seven (5.9%) employed an ankle support and eight (6.8%) other prophylactic measures (thermal support, biomechanical insole, etc.) according to their injury.